La responsabilité civile des dirigeants sociaux en droit OHADA - Akam Akam, André (Revue internationale de droit économique, 2007)
Keywords: Dirigeant social; Droit OHADA; Responsabilité civile

La mondialisation des affaires et les technologies de l’information - Akhrouf, Mohamed (La Revue des Sciences Commerciales, 2007)
L’économie nationale-ainsi que d’autres économies en développement –dépend de plus en plus des importations et des exportations .Aujourd’hui et à l’avenir , la prospérité de l’entreprise dépend de sa capacité de fonctionner sur le marché mondial. La mondialisation des économies accroit nettement la valeur d’information pour l’entreprise et offre de nouvelles occasions de croissance .Aujourd’hui les systèmes d’information procurent toute la puissance de communication et d’analyse dont les entreprises ont besoin pour conclure des échanges et diriger leurs affaires à l’échelle mondiale. La gestion des multinationales-la communication avec les distributeurs et fournisseurs , l’exploitation 24 heures sur 24 heures des succursales des différents pays , la satisfactions des besoins en matière de présentation des données sur les activités nationales et internationales –constitue un défi administratif considérable qui exige des réponses ultra-rapides de la part des systèmes d’information. La mondialisation et les technologies de l’information représentent aussi des menaces pour les entreprises commerciales .L e réseau planétaire de communication et les systèmes de gestion mondiaux permettent maintenant aux clients de faire leurs achats sur un marché mondial et d’obtenir des informations fiables sur les prix et la qualité des produits 24 heures sur 24 heurs . Ce phénomène ravive la concurrence et oblige les entreprises à se livrer à des échanges sur des marchés mondiaux ouverts et non protégés .Pour devenir des participants efficaces et rentables et rentables sur les marchés internationaux , les entreprises ont besoin des systèmes d’information et de communication puissants . Dans cet article, nous allons , d’abord , définir les principaux facteurs qui sous-tendent la mondialisation croissante des affaires et comparer les stratégies mondiales visant l’expansion et les développement de l’entreprise ; ensuite , nous montrons comment les systèmes d’information et les technologies de l’information soutiennent les différentes stratégies mondiales et comment planifier le développement des systèmes d’information internationaux . Enfin , nous allons évaluer les principales solutions techniques possibles pour la mise au point de systèmes internationaux .

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
Keywords: Harmonization; Investment; Member state

Libres propos sur la responsabilité contractuelle du pharmacien d’officine - Arbour, Marie-Ève (Revue de droit de l'Université de Sherbrooke, 2007)
Le pharmacien d’hier évoque l’image d’un professionnel passif, contraint d’exécuter fidèlement le traitement pharmacologique prescrit au patient par le médecin. Aujourd’hui, par contraste, la complexité des médicaments, le développement de la science et de la technologie, de même que les revendications croissantes des consommateurs ont contribué à un renouvellement des valeurs véhiculées par la profession pharmaceutique. Sur le plan de la responsabilité, l’étude du rapport contractuel entre le pharmacien et ses clients/patients met à jour un étrange paradoxe. D’un côté, la population revendique une relation davantage personnalisée avec le pharmacien ; de l’autre, les modes contemporains de distribution des produits de santé véhiculent des attitudes consuméristes ancrées dans la dépersonnalisation progressive de ce même rapport contractuel (i.e. Internet). Ces nouveaux paramètres créent une tension sur les principes traditionnels qui posent les paramètres de la responsabilité contractuelle du pharmacien. D’abord, ils invitent à une redéfinition du contenu obligationnel du contrat au regard de l’obligation d’information dont ces derniers sont progressivement débiteurs. Ensuite, les modalités de l’échange commercial contemporain posent le défi de préciser la portée des obligations déontologiques qui s’imposent aux pharmaciens dans l’acte de distribution à distance de médicaments, et ce, en l’absence d’une rencontre physique ayant eu lieu avec le patient. Enfin, le thème de l’indemnisation du préjudice corporel causé par le fait des médicaments défectueux invite à une analyse de la responsabilité du pharmacien en tant que sujet débiteur de l’obligation de qualité, tant au regard du C.c.Q. que de la L.p.c.. L’auteure conclut que ce fondement pluriel de la responsabilité contractuelle du pharmacien est principalement configuré par l’exigence (ou non) d’une ordonnance médicale. The pharmacist of yesteryear evokes the image of a passive professional, constrained to faithfully dispensing the medications prescribed by a physician. Today, however, the complexity of medications, the development of science and technology and the increasing demands of consumers have all contributed to the renewal of the fundamental values of the pharmaceutical profession. In terms of liability, an analysis of the contractual relationship between the pharmacist and his or her client/patient brings to light a paradoxical situation. One the one hand, patients appear to require a more personalized relationship with the pharmacist; yet on the other, contemporary modes of distributing drugs and healthcare products encourage consumerist attitudes resulting from the growing depersonalization of this very same contractual relationship (e.g. the purchase of medication on the internet). This new paradigm places stresses on the traditional principles underlying the contractual liability of the pharmacist. To begin with, it invites a redefinition of the obligational content in light of the duty to inform to which pharmacists are increasingly subjected. Moreover, the very characteristics of this contract are indicative of a need to better define the deontological duties imposed on pharmacists when dispensing medications to persons not physically present. Finally, product liability issues stemming from defective drugs invite further further analysis of a pharmacist’s responsibility as debtor of an obligation to ensure quality under both the Civil Code of Quebec and the Consumer Protection Act. The writer concludes that this multifaceted basis of a pharmacist’s contractual liability is determined primarily according to whether or not a a physician’s prescription is required.

Quinze ans de restructuration bancaire dans la CEMAC : qu’avons-nous appris ? - Avo, Désiré; Eyeffa Ekomo, Sylvie Marie-Louise (Revue d'économie financière, 2007)
Les pays de la Communauté économique et monétaire de l’Afrique centrale (CEMAC) ont connu, à partir du début des années 1980, une grave crise économique. Les conséquences de celle-ci se sont traduites, sur le secteur bancaire, par une dégradation rapide et brutale du portefeuille des banques. En réponse à cette crise, les autorités monétaires, avec l’appui de la communauté financière internationale ont engagé une politique de restructuration bancaire. Cette politique avait pour objectif d’assurer un retour à la stabilité bancaire en améliorant les circuits de financement. L’objectif de cet article est de montrer, après avoir présenté les différentes réformes qui ont été mises en oeuvre, que les restructurations bancaires, au lieu d’assurer le financement de l’économie, ont plutôt conduit à des paradoxes dont trois sont particulièrement développés. Il s’agit de : la surliquidité et le rationnement du crédit ; la concentration bancaire et le développement de la microfinance et enfin l’internationalisation bancaire sans développement des innovations financières. Fifteen years of banking restructuring in CEMAC : what have we learnt ? Member countries of the Central African Economic and Monetary Community (CEMAC) experienced a severe economic crisis since the 80’ s. As a consequence of this prolonged crisis, the portfolio of commercial banks dramatically deteriorated, therefore pushing monetary authorities and international community to envisage a restructuring strategy for the banking sector. The aim of this strategy was to stabilize the banking sector by improving financing channels and mechanisms. In this paper we show that the reforms implemented to restructure the banking sector, far from having improved financing mechanisms, have led to the emergence of three paradoxes : excessive liquidity of the system coupled with credit rationing, banking concentration and contemporaneous development of microfinance structures and foreign penetration in the banking sector without development of financial innovations.

La "déprofessionnalisation" de la qualité de transporteur routier de marchandises : une approche de l'article 2 (k) de l'Acte uniforme OHADA relatif aux contrats de transport de marchandises par route - Batouan, Joseph-Alain (Neptunus, 2007)
Keywords: AUCMR; Définition; Régime applicable aux acteurs; Rémunération du transporteur

Entreprise - Bouchard, Charlaine (Revue du notariat, 2007)

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.

Du patrimoine des sociétés de personnes et applications pratiques - Larochelle, Bernard (Revue du notariat, 2007)

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.

Arbitrage et procès équitable dans la zone sud-ouest de l’Océan indien - Zattara-Gros, Anne-Françoise (Revue internationale de droit comparé, 2007)
L’étude des rapports qu’entretiennent l’arbitrage et le procès équitable dans les différents droits des îles de la zone sud-ouest de l’Océan indien prend toute sa dimension dès l’instant où la zone offre un patchwork de systèmes juridiques différents. La question est alors de savoir si dans les droits des îles des Grandes Mascareignes, l’arbitrage revêt le costume juridique français, sachant que le Nouveau Code de Procédure civile (NCPC) édicté en France le 5 décembre 1975 a été, suite à l’accession à l’indépendance de ces différentes pays, transplanté à Madagascar, aux Comores et à Maurice. La logique conduirait à répondre par l’affirmative. Mais la diversité du contexte, constitué soit de transposition du droit français de l’arbitrage, qui intègre le modèle de procès équitable notamment défini par l’article 6 de la Convention européenne des droits de l’homme, soit d’érection d’un droit interne de l’arbitrage composé partiellement de dispositions juridiques françaises, offre des situations inédites. Si à l’instar des grandes tendances, l’étude croisée des dispositions relatives à l’arbitrage et celles du procès équitable dans l’Océan Indien révèle une perméabilisation croissante de ce deux dernières sphères, et de là un risque de processualisation de l’arbitrage, l’institutionnalisation de l’arbitrage permet également aux parties, de trouver des garanties, ce qui est pleinement satisfaisant dans des pays où l’État de droit est défaillant et la justice étatique mise à mal de façon à assurer la sécurisation juridique des investissements et des échanges commerciaux. The study of reports stating that arbitration and fair judgment exist in the different laws of the islands in the south western zone of the Indian Ocean takes on a whole new dimension if the zone provides a patchwork of different legal systems. The question is whether or not arbitration is the same as in the French legal system. One must consider that the New Civil Procedure Code (NCPC) which was decreed in France on 5th December 1975, was transplanted to Madagascar, the Comoros Islands and Mauritius. Logic would thus lead one to believe the affirmative. However the diversity of the context, which is constituted either by transposing French arbitration law that integrates the decreed trial model as defined by article 6 of the European Convention of Human Rights, or the erection of internal arbitration law composed partially of French legal dispositions, provides some new situations. If, in accordance with the trends, the cross study of dispositions relative to arbitration and those of the fair trial in the Indian Ocean reveal that these two spheres are growing, and that a result of this there is a risk of procedure arbitration, the institutionalization of arbitration also allows for the concerned parties to find guarantees, which is very satisfying for countries whose state law is weak and where state justice has difficulty in ensuring legal security for investments and commercial exchange.